Chinese national identity in the age of globalisation - Lu, Zhouxiang (Palgrave Macmillan, 2020)
Introduction: Constructing and Negotiating Chineseness in the Age of Globalisation – Yellow Peril or Yellow Revival? Ethnicity, Race and Nation in Late Qing Chinese Utopianism (1902-1911) – Shaolin, Wuxia Novels, Kung Fu Movies and National Identity – Social Network Service Platforms and China’s Cyber Nationalism in the Web 2.0 Age – Fostered Idols and Chinese Identity – Chinese National Identity and National Image in the Age of Globalisation – A New Chinese National Identity: The Role of Nationalism in Chinese Foreign Policy – Identity Narratives in China and the EU’s Economic Diplomacy – Comparing the BRI and the EU Connectivity Strategy for Asia – Nationhood and Ethnicity at the Frontiers: A Study of Hmong Identity in Western Hunan – ‘The People are God’ Third World Internationalism and Chinese Muslims in the Making of the National Identity in the 1950s – From ‘Small’ to ‘Big’ Nationalism: National Identity among China’s Hui Minority in the Twenty-First Century – The Complexity of Nationalism and National Identity in Twenty-First Century Xinjiang – Leveraging Mega-events to Embrace Chinese National Identity: The Politics of Hong Kong’s Participation in the Beijing 2008 Olympics and the Shanghai 2010 World Expo – The Evolution and Recognition of Self-identity in Food and Foodways of the Overseas Chinese – Temples and Huiguan: Negotiating Chineseness in Ho Chi Minh City – National identity, Religious Identity and Their Impacts on Subjective Well-being – A Case Study on Chinese Catholics in Ireland – Identity Reconstruction of Chinese Migrant Women in Ireland. Written by a team of international scholars from China, Germany, Ireland, New Zealand and the UK, this book provides interdisciplinary studies on the construction and transformation of Chinese national identity in the age of globalisation. It addresses a wide range of issues central to national identity in the context of Chinese culture, politics, economy and society, and explores a diverse set of topics including the formation of an embryonic form of national identity in the late Qing era, the influence of popular culture on national identity, globalisation and national identity, the interaction and discourse between ethnic identity and national identity, and identity construction among overseas Chinese. It highlights the latest developments in the field and offers a distinctive contribution to our knowledge and understanding of national identity. .
10.1007/978-981-15-4538-2
Keywords: China—History.; Ethnology—Asia.; Citizenship.; Kultur; Einflussgröße; Ethnizität; Ideologie; Diaspora; Chinesen; Relation; Globalisierung